DOES MARKETING CAPABILITIES MEDIATE ON THE ICT’S ADOPTION AND BUSINESS PERFORMANCE OF THE SMEs IN OMAN? CONCEPTUAL REVIEW (American International Journal of Business and Management Studies, 2022)
The main purpose is to review the empirical evidence and summarize the marketing capabilities' mediating effects on the adoption of ICTs and business performance of the Small and Medium Enterprises (SMEs) in Oman and develop a conceptual framework. Data were collected from the existing literature from different online sources. The study review findings revealed a significant gap in the literature regarding the full understanding of the simultaneous relationship among ICTs, marketing innovation, and business performance in SMEs. Most studies have concentrated on analyzing and discussing only one or two of these phenomena at a time. However, the other studies that have examined the simultaneous relationship among the three variables mentioned above have generally ignored the component of marketing capabilities, focusing instead on the idea of innovation in its broader sense. The present study findings also establish a lack of or insufficient empirical studies that broadly examine the contribution of ICTs adoption among SMEs and its effect on companies’ capabilities, such as marketing capabilities, and consequently its effect on business performance, especially in developing countries. Therefore, the present study is motivated to develop a conceptual framework for measuring the mediating effect of the marketing capabilities, ICTs adoption and business performance of SMEs in Oman one of the developing countries.JEL Classification Codes: M31.